INDUSTRI PERTAHANAN INDONESIA DALAM MEMBANGUN KEKUATAN MARITIM NASIONAL - Herbanu, R. Prabowo; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
Sovereignty is considered an important element of the state system. Sovereignty is an exclusive right in exercising the highest political authority. However, currently we are in a period of strategic limitations, where our sovereignty is disrupted due to the competitive advantage of our defense industry which has not become a priority. We are facing increasing global threats, marked by an international rules-based order that is dominated by the interests of certain countries, thus creating a more complex and unstable security environment. Responding to this, of course, it is very important Republic of Indonesia to make improvements and increase the superiority of national defense, especially in the maritime sector. This is because Indonesia is a country that has a large ocean and it is an obligation for all Indonesian citizens to always maintain its sovereignty. The method in this study uses secondary data from various literature sources to answer the efforts that can be made to build national defense in the maritime sector. The results of this study explain that Indonesia's maritime defense can be built through the intensification of various matters relating to the fulfillment of elements of maritime power. Of course, the Indonesian government and various related parties can consider this as soon as possible.